New Robotic Platforms for Gynecology. Are We Achieving One of the Golden Goals? - Rui Farinha; Luca Sarchi; Marco Paciotti; Carlo Andrea Bravi; Angelo Mottaran; Adele Piro; Luigi Nocera; Tommaso Calcagnile; Simone Assumma; Maria Chiara Sighinolfi; Siddhart Yadav; Stefano Terzoni; et al. (Clinical and Experimental Obstetrics & Gynecology)
Objective: To summarize the scientific published literature on new robotic platforms with potential use in gynecology and review their evolution from inception until the present day. The goal was to describe the current characteristics and possible prospects of these platforms. Mechanism: A non-systematic search of PubMed, Cochrane Library Central, EMBASE, MEDLINE, and Scopus databases was conducted to identify scientific literature on new robotic platforms and review their evolution from inception until January 2022. Only English-language publications were included in this analysis. The following keywords were used: “new robotic platforms”, “robot”, “Revo-I”, “Versius®”, “Senhance®”, “Single-Site”, “Single-Port”, “Multi-Port”, “EDGE SP1000”, “Flex®”, and “Hominis®”. Abstract reviews were conducted to determine the relevance of the review aims. Full-text analysis of all relevant English-language original articles was subsequently performed by one author (R.F.) and summarized after discussion with an independent third party (L.S., M.P.). No formal quality assessment of the included studies was conducted. Findings in brief: The Da Vinci robotic system is the leading platform in the robotic surgery market. Other new platforms have published peer-reviewed articles in the field of gynecology. Senhance® and Da Vinci SP® have the most substantial proof of their capacity to perform multi-incision and single-incision robotic surgery, respectively. Hominis® has the potential to play a major role in ultra-minimally invasive and scarless approaches. Conclusions: The significant advantages of Intuitive’s robots justify their worldwide dissemination. However, their drawbacks have motivated other companies to develop innovative solutions. Our research shows that the majority of these new platforms are still at the beginning of their technical and scientific validation but seem very promising.